2011
DOI: 10.1017/s1461145711000848
|View full text |Cite
|
Sign up to set email alerts
|

Acute administration of typical and atypical antipsychotics reduces EEG gamma power, but only the preclinical compound LY379268 reduces the ketamine-induced rise in gamma power

Abstract: A single non-anaesthetic dose of ketamine, a non-competitive NMDA receptor (NMDAR) antagonist with hallucinogenic properties, induces cognitive impairment and psychosis, and aggravates schizophrenia symptoms in patients. In conscious rats an equivalent dose of ketamine induces key features of animal models of acute psychosis, including hyperlocomotor activity, deficits in prepulse inhibition and gating of auditory evoked potentials, and concomitantly increases the power of ongoing spontaneously occurring gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 52 publications
6
66
1
Order By: Relevance
“…In a similar vein, the positive allosteric modulator TASP0433864 or orthosteric agonist at the metabotropic receptor 2 LY379268 completely reversed the ketamine-induced power increase in high-frequency bands [71,81,82] and partially reversed disrupted coherence [83]. …”
Section: P-eeg In Modeled Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, the positive allosteric modulator TASP0433864 or orthosteric agonist at the metabotropic receptor 2 LY379268 completely reversed the ketamine-induced power increase in high-frequency bands [71,81,82] and partially reversed disrupted coherence [83]. …”
Section: P-eeg In Modeled Animalsmentioning
confidence: 99%
“…Glutamate NMDA receptor antagonists such as PCP, ketamine, and MK-801 have utility in modeling the positive, negative, and cognitive deficits of schizophrenia in healthy man and laboratory animals [68,69,70,71,72]. In preclinical studies, acute administration of PCP elicited aberrant network oscillations in the higher gamma frequency range [73,74,75].…”
Section: P-eeg In Modeled Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that this association may reflect a cortical hyperexcitability that possibly disturbs the conscious experience [11]. Consistently, administration of typical and atypical antipsychotics reduced gamma power in patients with schizophrenia [17]. …”
Section: Introductionmentioning
confidence: 96%
“…In support of the aforementioned mechanisms, mGlu2/3 receptor agonists have been reported to inhibit excitatory neurotransmission in electrophysiologic studies (Kilbride et al, 1998;Kew et al, 2001;Benneyworth et al, 2007), to normalize excessive glutamate levels in the prefrontal cortex (PFC) in schizophrenia animal models (Moghaddam and Adams, 1998;Lorrain et al, 2003), and to reduce the aberrant PFC activity caused by N-methyl-D-aspartic acid (NMDA) receptor antagonists (Homayoun et al, 2005;Gozzi et al, 2008;Chin et al, 2011;Dedeurwaerdere et al, 2011;Jones et al, 2012). The relative contributions of mGlu2 and -3 to the mechanisms of action of mGlu2/3 receptor agonists remain unknown.…”
Section: Introductionmentioning
confidence: 99%